2011
DOI: 10.1007/s11596-011-0587-9
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the biomarkers associated with coronary artery lesions secondary to Kawasaki disease in Chinese children

Abstract: The biomarkers associated with coronary artery lesions (CAL) secondary to Kawasaki disease (KD) in Chinese children were investigated by using Meta-analysis. We searched documents published from January 1997 to December 2009 from medical electronic databases. According to inclusion and exclusion criteria, eligible full-text papers were identified. We conducted a comprehensive quantitative analysis by using Stata10.0 statistical software package to assess the heterogeneity among the documents, calculated the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 24 publications
4
23
0
Order By: Relevance
“…Serum CRP level is increased in patients with myocardial ischemia and sudden death due to coronary artery disease (28). Previous studies have shown that elevated ESR in KD patients is disadvantageous to the prognosis of CAL (29). In our study, CRP was significantly higher in patients with CAL, and it was also revealed that PLT was significantly higher in KD patients with CAL, possibly related to vascular inflammation and activation of the coagulation system.…”
Section: Discussionsupporting
confidence: 63%
“…Serum CRP level is increased in patients with myocardial ischemia and sudden death due to coronary artery disease (28). Previous studies have shown that elevated ESR in KD patients is disadvantageous to the prognosis of CAL (29). In our study, CRP was significantly higher in patients with CAL, and it was also revealed that PLT was significantly higher in KD patients with CAL, possibly related to vascular inflammation and activation of the coagulation system.…”
Section: Discussionsupporting
confidence: 63%
“…A host of traditional markers of inflammation and myocardial injury are higher in KD with than without coronary artery involvement, but not enough to guide decision making [54]. Baseline NT-proBNP also might help distinguish patients who develop coronary artery lesions (despite IVIG) from those who do not, but imperfectly [55].…”
Section: Kawasaki Diseasementioning
confidence: 99%
“…In patients with incomplete KD, the acute and sub-acute age-corrected hemoglobin levels were reduced; however, the sub-acute platelet counts increased in patients with complete KD. Furthermore, it is known that the platelet counts in KD patients are positively correlated with fever duration, and a longer inflammation period may be reflected in the increase in platelet counts (27). Jeon et al (28) observed that coronary artery aneurysms developed in 30 of 392 patients with KD within a month of diagnosis while in 20% they persisted even after 1 year of follow-up.…”
Section: Assignment -------------------------------------------------mentioning
confidence: 99%